Upaya Meningkatkan Kemampuan Motorik Kasar Anak Usia Dini Melalui Permainan Berlari dengan Rintangan di RA Uswatun Hasanah - Siti Muliyah (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This study aims to improve the gross motor skills of early childhood children through the implementation of an obstacle running game at RA Uswatun Hasanah, North Labuhanbatu. The study was motivated by the children's low gross motor skill levels, characterized by a lack of movement coordination, balance, agility, and confidence in performing physical activities. It employed the Classroom Action Research (CAR) method using the Kemmis and McTaggart model, comprising the stages of planning, action implementation, observation, and reflection. The subjects were 15 children from Group B, consisting of 8 boys and 7 girls. The study was conducted over two cycles, with each cycle consisting of two sessions. Data collection techniques included observation, documentation, and field notes, while data analysis was performed using both quantitative and qualitative descriptive methods. The results indicate that the obstacle running game successfully improved the children's gross motor skills incrementally. In the pre-cycle stage, the percentage of children achieving the